Sistemas integrados de produção revelando a biodiversidade fúngica antagonista a Rhizoctonia sp., Fusarium sp. e Sclerotium rolfsii no ecótono Cerrado/Amazônia - Berber, Gilcele de Campos Martin (2014)
Integrated systems have been considered as an alternative to reach better profitability and suitability of agricultural production systems. However, success depends on the knowledge of the processes involved in the management and conservation of soil quality. The antagonism among microorganisms or biological control can reduce the growth of pathogenic fungi that cause economic damage to crops. The aim of this study was to quantify fungi in the soil and identify potential antagonistic to Fusarium sp., Rhizoctonia sp. and Sclerotium rolfsii in monoculture and integrated production systems. During rain and dry season was assessed 10 production models, since the monoculture until the interactions between farming, livestock and forestry, as well a fallow area and other native vegetation. Quantification of colony forming units (CFU) had statistical difference among treatment and season period of soil sampling, being observed higher number of CFU for integrated system. Fungal isolates from soil of integrated systems have potential for biological control of plant pathogens as Rhizoctonia sp., Fusarium sp. and Sclerotium rolfsii. Antagonism was considered positive on presence of inhibition zone formation during paired culture. Identification of antagonist fungi showed that species were Penicillium, Talaromyces, Eupenicillium, Trichoderma, Aspergillus, Chaetomium, Acremonium, Curvularia, Purpureocillium, Bionectria, Paecilomyces, Plectospharella, Clonostachy, Mucor, Fennellia e Metarhizium.